Photodynamic Activity of Chlorophyllin and Polyethylenimine on Pseudomonas aeruginosa Planktonic, Biofilm and Persister Cells - Mahmoud, Mona; Richter, Peter; Lebert, Michael; Burkovski, Andreas (International Journal of Molecular Sciences, 2023)
Antimicrobial photodynamic inactivation is considered a promising antimicrobial approach that may not develop resistance in the near future. Here, we investigate the influence of the photosensitizer chlorophyllin (CHL) and the cationic permeabilizer polyethylenimine (PEI), exposed to a red light-emitting diode, on the human pathogen Pseudomonas aeruginosa free-living planktonic cells, the sessile biofilm and persister cells. The broth microdilution checkerboard method was used to test antimicrobial susceptibility. As a substrate for biofilms, the Calgary biofilm device was used, and the quantification of the biofilm biomass was carried out using a crystal violet assay. Serine hydroxamate was used for the induction of persisters. Our findings reveal that PEI ameliorates the antimicrobial activity of CHL against P. aeruginosa planktonic and biofilm states, and the concentration required to eradicate the bacteria in the biofilm is more than fourfold that is required to eradicate planktonic cells. Interestingly, the persister cells are more susceptible to CHL/PEI (31.25/100 µg mL−1) than the growing cells by 1.7 ± 0.12 and 0.4 ± 0.1 log10 reduction, respectively, after 15 min of illumination. These data demonstrate that CHL excited with red light together with PEI is promising for the eradication of P. aeruginosa, and the susceptibility of P. aeruginosa to CHL/PEI is influenced by the concentrations and the exposure time.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antimicrobial resistance; dormant bacteria; photosensitizer; stringent response